2019
DOI: 10.1002/alr.22436
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of chronic rhinosinusitis in patients with non‒cystic fibrosis bronchiectasis at a tertiary care center in the United States

Abstract: Background: Chronic rhinosinusitis (CRS) is associated with bronchiectasis; however, this relationship has not been well studied in the United States (US) population. In this work we aimed to determine the prevalence of CRS among patients with bronchiectasis affiliated with a US tertiary medical center and identify which comorbid diseases are associated with the presence of CRS in patients with bronchiectasis. Methods:This was a retrospective cohort study in which data were obtained from a large database wareh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…Steroid-dependent asthma is predominately mediated by eosinophilic airway inflammation and is more likely to be associated with bronchiectasis [ 30 ], indicating that eosinophilic airway inflammation is related to bronchiectasis formation in asthma patients. Similarly, recent data also found that peripheral eosinophil counts were elevated in patients with bronchiectasis and CRS [ 13 ]. Bronchiectasis may be induced by eosinophil infiltration and eosinophil-derived cationic proteins, lipid mediators, cytokines, chemokines, and growth factors [ 5 ].…”
Section: Discussionmentioning
confidence: 70%
“…Steroid-dependent asthma is predominately mediated by eosinophilic airway inflammation and is more likely to be associated with bronchiectasis [ 30 ], indicating that eosinophilic airway inflammation is related to bronchiectasis formation in asthma patients. Similarly, recent data also found that peripheral eosinophil counts were elevated in patients with bronchiectasis and CRS [ 13 ]. Bronchiectasis may be induced by eosinophil infiltration and eosinophil-derived cationic proteins, lipid mediators, cytokines, chemokines, and growth factors [ 5 ].…”
Section: Discussionmentioning
confidence: 70%
“…The concept of “united airway disease” or “one linked airway disease” has emerged, and allergic rhinitis, sinusitis, and asthma are expressed in different parts of the respiratory tract as one pathological process that is inflammatory in nature 12 . In addition, the concept has expanded beyond asthma, and an association with CRS has been reported in other lung diseases, including bronchiectasis 7 , 13 and COPD 8 . In a systematic review, the pooled prevalence of CRS in adults with bronchiectasis was 62%, and CRS was associated with a greater degree of bronchiectasis severity, poorer quality of life, reduction in olfactory detection, and elevated levels of inflammatory markers 7 .…”
Section: Discussionmentioning
confidence: 99%
“…We included individuals with a primary diagnosis of bronchiectasis, including those with primary ciliary dyskinesia. 45 This, together with comorbid respiratory conditions, including asthma, COPD, allergens or gastro‐esophageal reflux disease, 46 , 47 smoking history, 48 and frequency of acute exacerbations of bronchiectasis, 9 are all factors which are associated with chronic rhinosinusitis and may have contributed to the symptoms reported on the SNOT‐22 questionnaire. In the absence of collating this information, the extent to which the underlying cause of bronchiectasis and comorbid conditions contributed to symptoms of chronic rhinosinusitis or quality of life scores is not clear.…”
Section: Discussionmentioning
confidence: 99%